Enhancing Critical Raw Material Usage through Battery Cell Extraction and Reuse - Bunodiere, Alex; Duflou, Joost R. (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
This paper proposes a circular economy business model for recycling and remanufacturing Bosch Gen 3 batteries to enhance sustainability and economic viability. The model integrates collection, robotic disassembly, and state-of-health-based categorisation to extract the most valuable, reusable cells and then tests a battery remanufacturing option to maximize profit and critical raw material recovery. Two collection methods are analysed: incentivized returns (Option 1) and battery waste sorting at recycling centres (Option 2). A Monte Carlo simulation evaluates profitability with several uncertainties, including logistics and deposit refunds. Option 1 is more likely to obtain higher-quality cells, but is less likely to be profitable due to the high costs associated with the incentive, while Option 2 is more cost-effective, but yields lower-quality cells. This study highlights opportunities to optimize incentives and recycling value, providing a scalable framework for sustainable battery end-of-life management.